The association between diabetes and gastric cancer: results from the Stomach Cancer Pooling Project Consortium. Issue 3 (25th June 2021) - Dabo, Bashir; Pelucchi, Claudio; Rota, Matteo; Jain, Harshonnati; Bertuccio, Paola; Bonzi, Rossella; Palli, Domenico; Ferraroni, Monica; Zhang, Zuo-Feng; Sanchez-Anguiano, Aurora; Thi-Hai Pham, Yen; Thi-Du Tran, Chi; et al.
Abstract : Background: Prior epidemiologic studies on the association between diabetes and gastric cancer risk provided inconclusive findings, while traditional, aggregate data meta-analyses were characterized by high between-study heterogeneity. Objective: To investigate the association between type 2 diabetes and gastric cancer using data from the 'Stomach Cancer Pooling (StoP) Project', an international consortium of more than 30 case–control and nested case–control studies, which is large and provides harmonized definition of participants' characteristics across individual studies. The data have the potential to minimize between-study heterogeneity and provide greater statistical power for subgroup analysis. Methods: We included 5592 gastric cancer cases and 12 477 controls from 14 studies from Europe, Asia, North America, and South America in a two-stage individual-participant data meta-analysis. Random-effect models were used to estimate summary odds ratios (ORs) and their corresponding 95% confidence intervals (CIs) by pooling study-specific ORs. Results: We did not find an overall association between diabetes and gastric cancer (pooled OR = 1.01, 95% CI, 0.94–1.07). However, the risk of cardia gastric cancer was significantly higher among individuals with type 2 diabetes (OR = 1.16, 95% CI, 1.02–1.33). There was no association between diabetes and gastric cancer risk in strata of Helicobacter pylori infection serostatus, age, sex, BMI, smoking status, alcohol consumption, fruit/vegetable intake, gastric cancer histologic type, and source of controls. Conclusion: This study provides additional evidence that diabetes is unrelated to gastric cancer overall but may be associated with excess cardia gastric cancer risk.